2012
DOI: 10.1002/sej.1137
|View full text |Cite
|
Sign up to set email alerts
|

Who Changes Course? The Role of Domain Knowledge and Novel Framing in Making Technology Changes

Abstract: The foundations of established firms are laid when, early in life, venture executives explore dynamic landscapes in search of opportunities. During this search, the executive team processes information that might signal the need to change, and their cognitive flexibility in processing this information affects the likelihood of such changes. While executive backgrounds affect this information processing, current literature does not identify how executive backgrounds impact the extent of change a firm undertakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
99
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 128 publications
(171 reference statements)
3
99
1
Order By: Relevance
“…Research in related areas points to the possibility that an important but largely overlooked aspect of board composition may be the proportion of domain experts on a board, that is, the proportion of those directors whose primary professional experience is within the focal firm's industry and who are thus seen as possessing a high degree of competence in that domain (Evetts, Mieg, & Felt, 2006;Furr, Cavarretta, & Garg, 2012;Gerver & Bensman, 1954;Mieg, 2006). Recent research suggests that the proportion of domain experts in a strategic decision-making group can significantly shape Authors are listed in alphabetical order and contributed equally.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Research in related areas points to the possibility that an important but largely overlooked aspect of board composition may be the proportion of domain experts on a board, that is, the proportion of those directors whose primary professional experience is within the focal firm's industry and who are thus seen as possessing a high degree of competence in that domain (Evetts, Mieg, & Felt, 2006;Furr, Cavarretta, & Garg, 2012;Gerver & Bensman, 1954;Mieg, 2006). Recent research suggests that the proportion of domain experts in a strategic decision-making group can significantly shape Authors are listed in alphabetical order and contributed equally.…”
mentioning
confidence: 99%
“…This paper was made possible through a research grant from IESE Business School. a firm's strategic direction and its responses to the environment (Furr et al, 2012), which other research in turn has shown to be key determinants of organizational survival chances (Dencker, Gruber, & Shah, 2009;Haveman, 1992). This potential link between the presence of domain experts in strategic decision-making groups, such as corporate boards (Forbes & Milliken, 1999), and organizational survival is important to understand not only because ensuring survival is a critical concern for organizations (Hambrick & D'Aveni, 1992;Mellahi & Wilkinson, 2004) but also because the proportion of domain experts is a readily observable dimension of board composition that organizations can directly influence when creating a board or selecting new directors (see Almandoz, 2012;Pfeffer, 1972).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, "experienced decision-makers may be less likely to engage in counterfactual thinking" (Shepherd, Zacharakis, and Baron 2003, p. 382). This has also been observed in companies facing technological changes (Furr, Cavarretta, and Garg 2012) or disruptive business model innovation (Osiyevskyy and Dewald 2015). These authors distinguish between experience gained from working in the current industry (industry tenure) as opposed to exposure to other industries, and show how the first "could lead to cognitive rigidity, commitment to the status quo, and reluctance to making strategic changes" (Osiyevskyy and Dewald 2015, p. 66).…”
Section: 4-experience In the Business Strategy Frameworkmentioning
confidence: 94%